2023
DOI: 10.1177/09544119231157137
|View full text |Cite
|
Sign up to set email alerts
|

Exploiting multimodal CNN architecture for automated teeth segmentation on dental panoramic X-ray images

Abstract: Panoramic X-ray images are the major source used in field of dental image segmentation. However, such images suffers from the disturbances like low contrast, presence of jaw bones, nose bones, spinal bone, and artifacts. Thus, to observe these images manually is a tedious task, requires expertise of dentist and is time consuming. Hence, there is need to develop an automated tool for teeth segmentation. Recently, few deep models have been developed for dental image segmentation. But, such models possess large n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 38 publications
0
6
0
Order By: Relevance
“…Ahn et al [29] reported significant time savings with deep learning models in detecting mesiodens, with 1.5 ± 1.4 seconds for diagnosis compared to 811.8 ± 426.1 seconds for general practitioners. In semantic segmentation, various artificial models have been applied to automated teeth segmentation [32,33], dental caries detection [34,35], detection of third molars and mandibular nerves [36], dental restorations [37], and ectopic eruption of teeth [38]. They demonstrated effective performance with significantly reduced diagnostic time.…”
Section: Discussionmentioning
confidence: 99%
“…Ahn et al [29] reported significant time savings with deep learning models in detecting mesiodens, with 1.5 ± 1.4 seconds for diagnosis compared to 811.8 ± 426.1 seconds for general practitioners. In semantic segmentation, various artificial models have been applied to automated teeth segmentation [32,33], dental caries detection [34,35], detection of third molars and mandibular nerves [36], dental restorations [37], and ectopic eruption of teeth [38]. They demonstrated effective performance with significantly reduced diagnostic time.…”
Section: Discussionmentioning
confidence: 99%
“…Arora et al [33] presented an approach for automated teeth segmentation in dental panoramic X-ray images using a multimodal convolutional neural network (CNN) architecture.…”
Section: Discussionmentioning
confidence: 99%
“…However, its results still needed to be clarified on the coronoid and mandibular condyles, hence the use of the ensemble, which achieved an excellent result in their research. Similarly, Arora et al [38] used a model based on an encoder-decoder architecture. Its encoder part contained several types of CNN-based models to exploit each network and combine their output to generate a fine-grained contextual feature for teeth segmentation.…”
Section: Other Approachesmentioning
confidence: 99%
“…The segmentation of teeth can be considered a pixel-wise classification problem where the model tries to classify whether the given pixel belongs to the background or teeth class. When dealing with medical image segmentation, some approaches use the standard Cross Entropy (CE) [44,38]. In contrast, others use metric-sensitive, minority-class penalizing losses, or a mixture between metricsensitive and Cross Entropy losses [1, 45,19,20] which have shown significant performance in dealing with hard-to-segment regions.…”
Section: Loss Functionmentioning
confidence: 99%